Flexible Efficient Top-Emitting Organic Light-Emitting Devices on a Silk Substrate - Liu, Yue-Feng; An, Ming-Hui; Bi, Yan-Gang; Yin, Da; Feng, Jing; Sun, Hong-Bo (IEEE photonics journal, 2017)
A flexible efficient top-emitting organic light-emitting device (TOLED) on an off-the-shelf silk substrate has been demonstrated by planarizing the silk substrate with photopolymer NOA63. The flexibility of the bare silk substrates was retained in the planarized silk substrates due to ductile characteristics of cured NOA63. The planarized silk substrate has shown superiority on surface morphology, which is beneficial to the performances of OLEDs. Their maximum luminance and current efficiency are 45545 {\rm{cd/ m}}^{2} and 37.7 cd/A, respectively. Moreover, our devices show not only high luminance and efficiency but also high flexibility and mechanical robustness. Emission of operating devices is uniform and free of defects under a very small bending radius and the luminance and efficiency do not deteriorate obviously after repeated bending. TOLEDs on silk substrate are a potential alternative to wearable displays.